Studi Perbandingan Efisiensi Perbaikan Mutu Air Limbah Domestik melalui Filtrasi Horizontal dengan Beton Porous Recycled Aggregate Berlapis - Hakim, Ariza Julian; Cahya, Evi Nur; Haribowo, Riyanto (Fakultas Teknik, Universitas Brawijaya, 2021)
Domestic wastewater pollution is one of the reasons for the decline in the national Water Quality Index. The increasing number of people with inadequate sanitation facilities requires a solution. Porous concrete with RCA aggregate has the potential to improve domestic wastewater. Made of porous concrete, the filter is made with dimensions of 40Ã—40Ã—5 cm3 using RCA aggregate with 0.5-2.0 cm gradation. Two reactor models of the same size were prepared, containing 3 and 4 layers of filters. Domestic wastewater as a test object comes from Tlogomas Integrated Sewer System, flowed continuously into the model. The results of Test 1 show that the 3-Filters Reactor Model can improve the pH and COD values according to the quality standard, while the 4-Filters Reactor Model can only improve the pH value. The results of Test 2 show that the 3-Filters Reactor Model can improve the pH and TSS values according to the quality standard, while the 4-Filters Reactor Model can only improve the pH value. The average efficiency of the filtration against influent shows that the 3-Filters Reactor Model is better than the 4-Filters Reactor Model with the percentage of improvement in pH 11.54%, BOD 26.15%, COD 20.79%, and TSS 46.37%. However, in sediment trapping, the 4-Filters Reactor Model is superior with 112 mm compared to the 3-Filters Reactor Model which is 100.5 mm.